Rural homestays reviving culture and traditions: A study analysing expectation and satisfaction of homestay’s guests - Singh, Ritika; Sajnani, Manohar; Gupta, Pawan (Linguistics and Culture Review, 2021)
In contemporary world, travellers are more inclined towards seeking peace and tranquility from vacation destination rather than mere travel. Travelllers indulge in travel experience that enables them to connect with locals, gets genuine insight into their culture and traditional lifestyles. Rural homestays are one such means to cater the needs of such tourists in all-inclusive. The purpose of the study is to evaluate variation between the factors affecting satisfaction and expectation of the homestay’s guests. The study is conducted in the Shimla district of Himachal Pradesh, India. The data is collected by close ended questionnaire method, in face-to-face interaction with 200 tourists staying in 20 rural homestays. The study is intended to evaluate various attributes of the rural homestay accommodation that leads to satisfaction/dissatisfaction among guests staying in the homestay and also to make homestay owners understand the needs and requirements of guests to improve upon the service provided. The study also analyses the relationship between guests’ socio-economic profile and their satisfaction. The result of the research supports the suggestions for the homestay owners and public administrators that further boost the level of satisfaction of the guests and contributes in extensive rural as well as cultural tourism development.